Development of Merdeka Curriculum Teaching Module Based on Problem Based Learning Acid-Base Material - Lusianti, Lusianti; Enawaty, Eny; Ulfah, Maria; Hairida, Hairida; Erlina, Erlina (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Teachers experience difficulties in designing teaching modules in the independent curriculum and teachers need differentiated teaching modules. This research aims to develop an Merdeka Curriculum Teaching Module Based on Problem Based Learning on Acid and Base Material and determine the feasibility of the teaching module and the teacher’s response to the teaching module. The research method used is Research and Development (R&D) with the ADDIE model limited to the development stage. The subject of this research is the Independent Curriculum teaching module based on Problem Based Learning on acid base material. The research instrument used was a questionnaire. This questionnaire is used to validate the product and test teacher responses using a Likert scale. The data collection technique used was indirect communication techniques by providing questionnaires. Data from product validation results were analyzed using Gregory with validation results from the material aspect of 1 and the media aspect of 1 with the high validity category. Then a trial was carried out with a response test carried out on 2 chemistry teachers. The teacher response test results obtained a percentage of 100%. This shows that the Merdeka Curriculum teaching module based on problem-based learning on acid-base material meets appropriate for use as a teaching tool.